Stimulation of Osteogenic Differentiation of Induced Pluripotent Stem Cells (iPSCs) Using Bioactive Glasses: An in vitro Study - Kargozar, Saeid; Lotfibakhshaeish, Nasrin; Ebrahimi-Barough, Somayeh; Nazari, Bahareh; Hill, Robert G. (Frontiers in Bioengineering and Biotechnology, 2019)
Selection and use of an optimal cell source for bone tissue engineering remain a challenging issue; the invention of induced pluripotent stem cells (iPSCs) have created new hopes on this regard. At the present study, we attempted to show the usability of iPSCs in combination with bioactive glasses (BGs) for bone regeneration applications. For this aim, iPSCs were cultured and incubated with the strontium and cobalt-containing BGs for different intervals (1, 5, and 7 days). The cell cytotoxicity and attachment were assessed using MTT assay and scanning electron microscopy (SEM), respectively. Moreover, the osteogenic differentiation of iPSCs seeded onto the glasses was evaluated using alkaline phosphatase (ALP) activity assay and real-time PCR. The obtained results clarified that although the cell viability is decreased during a 7 day period, the iPSCs could adhere and expand onto the BGs particles and over-express the osteogenic markers, including osteocalcin, osteonectin, and Runx2. Based on the data, we conclude that iPSCs in a combination of BGs can be considered as a potential candidate for bone tissue engineering strategies.